A simple reflection on climate change - Barcellos, Afonso Lopes; Saccol, Renata da Silva Pereira; Carvalho, Nathalia Leal; Rosa, Luana Filippin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
In order to discuss climate change and our role, this literature review was developed. The term climate change, climate change or climate change refers to global-scale climate change or Earth's regional climates over time. These variations refer to changes in temperature, precipitation, cloudiness and other climatic phenomena in relation to historical averages. Such variations can alter climatic characteristics in a way to change their didactic classification. These changes can be caused by processes internal to the Earth-atmosphere system, by external forces, or by the result of human activity. Therefore, it is understood that climate change can be either an effect of natural processes or arising from human action and so one should keep in mind what kind of climate change is being referred to.